LANGUAGE AS THE MIRROR OF A NATION: THE STRATEGIC ROLE OF THE STATE LANGUAGE IN SOCIAL DEVELOPMENT - Dilshod Zarif o'g'li Kushanov; Halim Zarif o'g'li Xurramov; Zaripova Aziza Shaxobiddinovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article investigates the role of language not only as a tool for communication  but  as  a  symbol  of  state  independence,  the  foundation  of  national identity, and a driver of social progress. The article analyzes the legal status of the Uzbek  language,  its  role  in  public  administration,  education,  science,  and  digital technologies.  Furthermore,  it  justifies  the  strategic  importance  of  preserving  and developing the state language in the context of globalization.